Do not dismiss the commitment to the humanisation of medicine - Sgreccia, Elio (Medicina e Morale, 1986)
News of the new achievements and successes of cutting-edge medicine are taking a back seat, or being forgotten, to the day-to-day problems of healthcare management outside and inside hospitals.